Gamification for the Ancient Kingdom of Nusantara with User-Centered Design Approach - Arifin, Yulyani; Martin, Martin; Ryan, Ryan; Dratama, Ryan (Bina Nusantara University, 2018)
The purpose of this research was to conserve the history of Nusantara kingdoms with the interesting way for the students. The researchers proposed a method by combining the history of ancient kingdoms in Nusantara with the game. It was done by using gamification with the user-centered design approach. The data collection used questionnaires and literature review. Moreover, the researchers identified the resources by applying the gamification element, developing the game based on user requirement, and evaluating the usability testing. The result shows that the implemented gamification in learning Nusantara can attract the students to learn about history. Based on the result of usability testing that has already been tested using the prototype, it proves that the user interest to learn the history of the ancient kingdom in Nusantara is increased. The results also imply that gamification indeed is one of a suitable method to be used as a medium for students to learn about history, especially the ancient kingdoms in Indonesia.